اللاجئون في السودان : دوافع اللجوء و تهديده للأمن القومي - موسى، بدرالدين بخيت (مركز الراصد للدراسات السياسية والاستراتيجية, 2009)
This study deals with the history of refugee phenomenon into the Sudan from neighbouring African countries: its causes dargetsats negative and positive effects and how it affects Sudanese national security . The study also looks into Sudanese and international policies towards refugees and whether the Sudan had done its duty in receiving them on behalf of the internationl family ;having in mind that taking care of refugees is an international responsibility.
Keywords: الأحوال الاقتصادية -- اللاجئون -- الصراع السياسي -- السودان -- الاضطهاد الديني -- الأمن القومي